Iranian Researchers' Contribution to Otorhinolaryngology: A Bibliometric Survey (2011-2020) - Peyvandi, Ali Asghar; Shamloo, Zahra; Khajavi, Mahdi; Mokhtarinejad, Farhad; Saberi, Mohammad Karim; Haseli, Davoud; Mokhtari, Heidar; Ouchi, Ali (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2024)
Background: Iranian researchers' scientific output in otorhinolaryngology needs to be evaluated from a bibliometric perspective. Aim: This survey aimed at studying Iranian researchers' global contribution to the field during the recent decade (2011-2020). Methods: Data were extracted by conducting a formulated search strategy in Scopus and analyzed by applying some bibliometric approaches and depicting scientific visualizing maps in VOSviewer software package. Results: Iranian researchers published 2488 documents on otorhinolaryngology during 2011-2020. The mean h-index of the documents was 42, with mean citations per document=6.60. The majority of documents were original research (87.78%) and in English (.96.70%). The annual growth of Iranian researchers' documents on otorhinolaryngology was increasing in the studied years (R2=0.91), especially in 2019 and 2020. Nader Saki from Ahvaz Jundishapur University of Medical Sciences with 65 documents (citations per document=18.42 and h-index=11) ranked first among top authors. Iranian Journal of Otorhinolaryngology was the first-ranked journal with publishing 327 documents. Among research institutes, Tehran University of Medical Sciences ranked first with 631 documents. The first-ranked collaborating country was the USA collaborating with Iran in authoring 125 documents. Broad-ranged keywords covering almost all aspects of the field were used in the published documents that were included in four topic clusters. Conclusions: The global research on otorhinolaryngology made by Iranians has found its way. This study recognized important authors, journals, institutions, and countries as well as highly frequent co-occurred keywords and main subject clusters included in otorhinolaryngology documents published by Iranian researchers in the field.